Pests interaction with fertilization levels in the association maize-cowpea (Zea mays L. Vigna unguiculata (L.) Walp.) - Martínez Tambito, Edgar A. (Universidad de Costa Rica, San José (Costa Rica) CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE; UCR, Turrialba (Costa Rica), 1982